(untitled) (Journal of Fatima Jinnah Medical University, 2024)
Background: Chronic obstructive pulmonary disease (COPD) is known as an obstructive pulmonary disease it causes particular small airway obstruction. Currently available medications for COPD are not able to reduce the progressive deterioration of lung function. The current study aims to determine the effectiveness of doxofylline and theophylline in improving the pulmonary functions in stable COPD patients. Methods: A Randomized controlled trial was conducted on a total of 80(40 in each group). Stable COPD patients (FEV1/FVC < 0.70) patients visiting the outpatient department of Sir Ganga Ram Hospital for treatment and fulfilling inclusion criteria were enrolled to participate in the study. Both groups were given standard long-acting bronchodilator therapy such as salmeterol inhaler 25mcg twice daily. Group A was given theophylline, while group B was given doxofylline. Independent sample t-test was applied to compare the spirometry findings in both groups by using SPSS 25.0. A p-value of <0.05 was considered statistically significant. Results: In current study it was reported that the 36 (45.0) of patients were 30-40 years old. The majority of patients were male 68(85.0%) and suffered from COPD. There was an increased improvement in spirometric parameters among both groups. The both groups have same effect on spirometric parameters in terms of FEV1, FVC, FEV1/FVC and FEC1% prediction. Both drugs increase the spirometry functionality. (p-value > 0.05). There was significant difference among side effect of both groups. Doxophylline was found to have fewer side effects compared to theophylline. (P value< 0.05) Conclusion: It was concluded that the both drugs theophylline and doxofylline revealed consistent improvement in spirometric outcomes (FEV1, FVC, and the FEV1/FVC ratio) with the passage of time in COPD. The current study demonstrates that both drugs have a equal efficacy and safety profile than theophylline in patients with COPD.